The Islets of Langerhans - Islam, Md. Shahidul; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2010)
This book is a unique and thoughtful blend of critical background information and advances made in a multitude of areas of contemporary islet research. It is an essential reference book, the first of its kind in many years, for professionals as well as for the beginners interested in the study of islet physiology and diabetes. The book is unique in its breadth: it deals with anatomy, histology, ultra-structure, evolution and comparative anatomy, imaging, developmental biology, programming, apoptosis, mitochondrial function, metabolism, cellular signaling, electrophysiology, oscillation of hormone secretion, islets of model animals, immunology, proteomics, regenerative medicine, clinical advances, islet transplantation, and finally islet tumors. Individual chapters contributed by over a hundred experts and enthusiasts, not only provide a balanced view of the recent advances made in the respective fields, but also provide directions and thoughts for future research. Thanks to vivid and colorful illustrations, tables and sketches, the book as a whole, and the individual chapters make reading a pleasant experience. It is a valuable compilation that one would love to possess personally and buy as a present to a colleague.
Microscopic Anatomy of the Human Islet of Langerhans -- The Comparative Anatomy of Islets -- Approaches for Imaging Islets: Recent Advances and Future Prospects -- Islet Cell Development -- High Fat Programming of ?-Cell Failure -- Nutrient Regulation of Insulin Secretion and ?-Cell Functional Integrity -- Electrophysiology of Islet Cells -- ATP-Sensitive Potassium Channels in Health and Disease -- Role of Mitochondria in ?-cell Function and Dysfunction -- Basement Membrane in Pancreatic Islet Function -- Calcium Signaling in the Islets -- Electrical Bursting, Calcium Oscillations, and Synchronization of Pancreatic Islets -- Cyclic AMP Signaling in Pancreatic Islets -- Exocytosis in Islet ?-Cells -- The Novel Roles of Glucagon-Like Peptide-1, Angiotensin II, and Vitamin D in Islet Function -- Proteomics and Islet Research -- Wnt Signaling in Pancreatic Islets -- Molecular Pathways Underlying the Pathogenesis of Pancreatic ?-Cell Dysfunction -- Mechanisms of Pancreatic ?-Cell Apoptosis in Diabetes and Its Therapies -- ?-Cell Function in Obese-Hyperglycemic Mice [ob/ob Mice] -- Islet Structure and Function in the GK Rat -- The ?-Cell in Human Type 2 Diabetes -- Clinical Approaches to Preserve ?-Cell Function in Diabetes -- Immunology of ?-Cell Destruction -- Toll-Like Receptors and Type 1 Diabetes -- Prevention of ?-Cell Destruction in Autoimmune Diabetes: Current Approaches and Future Prospects -- In Vivo Regeneration of Insulin-Producing ?-Cells -- Customized Cell-Based Treatment Options to Combat Autoimmunity and Restore ?-Cell Function in Type 1 Diabetes Mellitus: Current Protocols and Future Perspectives -- The Programmable Cell of Monocytic Origin (PCMO): A Potential Adult Stem/Progenitor Cell Source for the Generation of Islet Cells -- Islet Isolation for Clinical Transplantation -- Human Islet Autotransplantation: The Trail Thus Far and the Highway Ahead -- Modulation of Early Inflammatory Reactions to Promote Engraftment and Function of Transplanted Pancreatic Islets in Autoimmune Diabetes -- Successes and Disappointments with Clinical Islet Transplantation -- Islet Cell Tumours.
Keywords: Medicine; Diabetes; Cytology; Biomedicine; Biomedicine general; Diabetes; Cell Biology; Cell Physiology